Urgency of Online Petition to guarantee the Freedom of Speech and Participate Rights in Government - Arrsa, Ria Casmi; Listiningrum, Prischa; Siswanto, Azzahrasya Sophia (Human Rights in the Global South (HRGS), 2022)
The freedom to express ideas and participate in the government is often manifested through democratic voting or involvement in general elections, but the processes taking place in elections cannot fully ensure that the members of the public can get their rights to the freedom of speech and participation in the government. With doctrinal legal method, this research has found that there seems to be an urgency to initiate an online petition platform in Indonesia as an alternative channel accessible to all the members of the public in order to optimize the exercise of the freedom of speech and equal participation in the government. Online petition systems have been around in Indonesia for quite some time, initiated and managed by change.org as a private organization along with other non-governmental organizations, but the legal loophole regarding online petitions that represent public participation in forming policies has not been capable of guaranteeing the attention or responses from the government over particular issues. In order to gain more perspectives, this article compare the online petition systems in the US and South Korea that were initiated by presidential agencies, and also the online petition in Germany that is under the direct management of the Petition Committee bellow the parliament (Bundestag). Therefore, it is concluded that Indonesian president has the power to rule the government in order to respond the urgency to give protection and fulfill Human Rights, especially freedom of speech and the rights to participate in the government by setting the legal basis.